Życie w lesie, czyli o wolności Henry’ego Davida Thoreau - Czarnecka, Agnieszka (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
In order to become a member of the Transcendental Club, established in 1836 by Ralph Waldo Emerson, one had to be a free-spirited person. The author argues that Henry David Thoreau not only satisfied the required criterion, but he also made his own contribution to the philosophy of freedom. In this paper, Thoreau’s conception of freedom is interpreted in economic, social, moral, and political terms. The author argues that for Thoreau philosophy was a highly practical activity and for this reason his vision of freedom refers to the broader context of living a good life. The first part of the article problematizes the philosopher’s critical attitude toward the free market economy, as well as his solutions (simple maxims and practices) intended to help people save two aspects of their freedom, namely the ability to choose one’s own idea of a good life and work-life balance in the nineteenth-century society. The second part is focused on the analysis of one among Thoreau’s particular prescriptions, that is walking, understood as the need for “wilderness” (independent thinking and action) within social freedom. The two following parts of the paper concern political issues, in particular, civil disobedience and abolitionism. At this point, the role of the conscience and its superiority over positive law are discussed
Keywords: Thoreau, Henry David (1817-1862); sumienie; niewolnictwo; wolność; natura; dobre życie; nieposłuszeństwo obywatelskie